2012
DOI: 10.1007/s12663-012-0345-y
|View full text |Cite
|
Sign up to set email alerts
|

Chordoma Arising from Cranial Base Extending to Oropharynx: An Unusual Presentation

Abstract: Chordoma is a relatively rare tumor of the skull base thought to originate from embryonic remnants of the notochord. Chordomas arising from the skull base/clivus are typically locally aggressive with lytic bone destruction. When chordomas occur in an extraosseous location, they may mimic other lesions of the nasopharynx and oropharynx. We present a case of primarily extraosseous chordoma involving the oropharynx in an effort to improve the preoperative diagnosis of this rare tumor among the dental fraternity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…To the best of our knowledge, there have only been 20 reported cases of this type of tumor in the medical literature ( 26 ). Late diagnosis is due to the non-specific and insidious onset of signs and symptoms and the slow growth rate of the tumor ( 13 , 25 ), which is typically only detected when it has grown to a size large enough to cause a notable effect to the surrounding tissues. In the present case report, the patient presented with cranial neuropathies, pain and difficulty swallowing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there have only been 20 reported cases of this type of tumor in the medical literature ( 26 ). Late diagnosis is due to the non-specific and insidious onset of signs and symptoms and the slow growth rate of the tumor ( 13 , 25 ), which is typically only detected when it has grown to a size large enough to cause a notable effect to the surrounding tissues. In the present case report, the patient presented with cranial neuropathies, pain and difficulty swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative radiotherapy with photon or proton beam currently serves an important role in chordoma management and has been reported to show a positive outcome ( 2 , 4 , 13 , 19 ). Radiotherapy for head and neck cancer, such as in the present case report, is a challenging task due to the complex anatomy of the head and neck region, with these tumors being located in close proximity to radiation dose-limiting critical structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chordomas located in an atypical position are called ectopic chordomas, such as OCs. The morbidity rate associated with chordomas is approximately 0.2% of all nasopharyngeal and oropharyngeal masses, [ 3 ] and they most commonly occur in 50- to 60-year-old patients; however, Naka et al [ 4 ] reported the occurrence of chordomas in patients 4 to 80 years old with a median age of 51 years. OCs have been sporadically reported in the literature, with the first report originating in 1959.…”
Section: Discussionmentioning
confidence: 99%
“…Bulundukları anatomik bölgeye göre sakrokoksigeal, sfenooksipital veya vertebral olarak sınıflandırılırlar. Kordomanın en sık görüldüğü bölge sakrumdur; kafa tabanı, klivus bölgesi ikinci en yaygın anatomik bölgedir 2 . Servikal bölge yerleşimli kordomalar oldukça nadir görülmektedirler.…”
Section: Introductionunclassified